IMPLEMENTATION OF PUBLIC SERVICES IMPLEMENTATION POLICY AT PUSKESMAS GEDONG PANJANG, SUKABUMI CITY - Ida Halimah; Ike Rachmawati; R. Deni Muhammad Danial (CV KULTURA DIGITAL MEDIA, 2022)
This study aims to describe the implementation of public service delivery policies at the Gedong Panjang Public Health Center, Sukabumi City, and also to identify the factors that drive and hinder it. This study uses a qualitative method, which aims to describe certain circumstances. This study focuses on compliance and duties and functions as well as the factors that influence the implementation of public service delivery policies at the Gedong Panjang Public Health Center, Sukabumi City. The results showed that the implementation of Perda no. 9 of 2019 concerning the Implementation of Public Services at the Gedong Panjang Public Health Center, Sukabumi City is quite going well, seen from the dimensions of compliance and routine functions, namely the availability of service standards that are a reference in providing services to the public and the Gedong Panjang Health Center officials have understood and carried out their main duties and functions. . Although there is still no provision for the fulfillment of service obligations and publication of the results of the community satisfaction survey and there are no adequate facilities/facilities to support performance. Meanwhile, the driving factors for the implementation of public service delivery policies are consistent with policy content messages in policy delivery, information on how to work, appointment/placement of staff according to competence, and standard procedures for implementing policies. Furthermore, several factors that hinder the process of implementing public service delivery policies are lack of socialization, limited diversity in communication channels, inadequate number of human resources, and inadequate supporting facilities.